Research Progress on the Association Between Appendectomy and Mental Disorders - Cai, Jiaman; Wang, Zhongling; Chen, Daorong (Journal of Contemporary Medical Practice, 2025)
Appendectomy, a common procedure in general surgery, has traditionally been regarded as a safe treatment for acute appendicitis. In recent years, with the advancement of research on the microbiota-gut-brain axis (MGBA), increasing attention has been given to the potential impact of appendectomy on mental health, as the appendix plays a crucial role in intestinal immunity and microbiota regulation. This review seeks to examine recent advancements in research on the relationship between appendectomy and mental disorders, providing new insights into the clinical decision-making process for the treatment of appendicitis.